Luo Mu’s Landscape in the Styles of Ni Zan and Huang Gongwang - Wang, Ching-Ling (The Rijksmuseum Bulletin, 2023)
Ching-Ling Wang explains how Chinese painters learned their craft by imitating the styles of esteemed masters from the past. A landscape painting with an inscription by Luo Mu in the Rijksmuseum collection reveals that there was also a pursuit to find a disctinctive, personal painting style.